VALIDITY ANALYSIS OF THE DIGITAL MATERIAL DEVELOPMENT ON INDONESIAN LANGUAGE SKILLS LEARNING SUBJECT BASED ON MALAY CULTURE FOR PGSD STUDENTS - Eva Astuti Mulyani; Mahmud Alpusari; Dede Permana (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This paper discusses the validity analysis of digital products in Malay culture-based Indonesian Language Skill courses through PjBL for University Elementary School Teacher Education students. The research was conducted in the Elementary School Teacher Education Study Program in July-October 2022. The development model applied in the research of this paper was the research model and educational development developed by Bord and Gall, which consists of three stages namely preliminary studies, product development, and product implementation. In the research of this paper, the researchers limited only the product development stage. The data collection technique used was a research instrument in the form of a validation sheet used by material and media experts in assessing digital teaching materials. Validation instruments were given to media and material experts. Based on the analysis results, it shows that the percentage was obtained completely from the assessment by the validator of digital material development for Indonesian-language skills courses based on Malay culture and PjBL with an average percentage score of 88.82% that is categorized as very suitable to use as digital teaching materials. Nevertheless, there are several parts of the digital material that need to be revised in order to complete the digital material. In the end, the revision results of this digital material can be applied in the Indonesian Language Skills course for the students at PGSD FKIP Study Program in Universitas Riau and can be applied in the lecture system.Â